Evaluasi Sistem Jak Lingko terhadap Perubahan Perilaku Pengguna Mikrotrans di Jakarta Selatan: Analisis Dampak Sosial dan Ekonomi terhadap Kualitas Pelayanan - Murdiono; Aris Sunarya; Ika Devy Pramudiana; Dendy Patria (NAAFI: JURNAL ILMIAH MAHASISWA, 2024)
This study aims to evaluate the “Jak Lingko” system and its impact on the behavioral changes of Mikrotrans users in South Jakarta, with a primary focus on the social and economic effects as well as the quality of public transportation services. This research employs a qualitative method with a descriptive-analytical approach, aimed at describing and analyzing changes in user behavior following the implementation of the Jak Lingko integration system. James S. Coleman's Rational Choice Theory is used as an analytical framework to understand users' decisions and preferences in selecting transportation modes. The findings reveal that the Jak Lingko system influences users' travel patterns by improving comfort, time efficiency, and accessibility between transport modes. However, challenges such as users’ limited understanding of the system’s mechanisms and incomplete integration on some routes remain to be addressed. Socially, the system enhances urban mobility, reduces congestion, and broadens transportation access for low-income groups. Economically, the system results in travel cost savings for users, increased operational efficiency, and the potential for long-term government subsidy reductions. Overall, the Jak Lingko system has a significant positive impact on public transportation users' behavior and offers solutions to several urban transportation challenges. However, to maximize its benefits, sustained efforts are needed to increase public awareness, strengthen accessibility infrastructure in underserved areas, and conduct continuous evaluations of the system’s performance. This study recommends collaboration between local governments, transportation operators, and the community to ensure the sustainability and effectiveness of the Jak Lingko program in the future